ASSOCIATION BETWEEN PERIODONTITIS AND GESTATIONAL DIABETES MELLITUS - Sharjeel, Muhammad; Ataullah, Khurram; Ahmed, Myra (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate association between periodontal disease and gestational diabetes mellitus.Study Design: Case control study.Place and Duration of Study: This study was carried out at Department of Periodontology, Fatima MemorialHospital, Lahore, from Jul 2016 to Jan 2017.Methodology: A total of 140 patients divided into 2 groups i.e., cases & controls (70 in each group) were included the study. Periodontal examination was carried out by a WHO periodontal probe and clinical measurements of periodontal conditions including Bleeding on Probing (BOP), Probing Depth (PD) and Clinical Attachment Level (CAL) were recorded. A single periodontology resident took all the said measurements.Results: Patients ranged between 20-45 years of age. Mean age of the patients was 31.37 ± 5.07 years and 31.57 ± 4.27 years in cases and controls, respectively. In cases periodontitis was found in 52 patients (74.3%) while 37patients (52.9%) were having periodontitis in control group. There was an association between periodontal disease and gestational diabetes mellitus (GDM) (odds ratio 2.58).Conclusion: In conclusion, periodontitis in pregnancyis found to increase the risk for gestational diabetes mellitus compared to women without periodontitis.